PENDIDIKAN KARAKTER DALAM KUMPULAN CERITA PENDEK IHWAL NAMA MAJID PUCUK KARYA T. AGUS KHAIDIR - Iskandar, Surya; Suhardi; Dwi Leoni, Tessa; Zaitun; Leo Shanty, Isnaini; Wahyusari, Ahada (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines a published short story that has received the best award among other short stories selected by Kompas, and the short story "Ihwal Nama Majid Pucuk" by T. Agus Khaidir is rich in character education values. The purpose of this study is to conduct an in-depth description of the various character education values contained in the short story collection "Ihwal Nama Majid Pucuk" by T. Agus Khaidir. This research is qualitative and uses descriptive methods. The instrument used is the researcher himself, supported by an analysis guide table that helps the researcher summarize the data obtained. The data in this study are in the form of dialogue excerpts or sentences from the Short Story Collection "Ihwal Nama Majid Pucuk" by T. Agus Khaidir, which consists of 20 short stories. The data collection technique used to obtain research data uses listening and note-taking techniques. In this study, the researcher uses qualitative analysis techniques, which means data processing techniques used to understand complex phenomena. The steps in analyzing data are presenting the data to be analyzed, grouping the data and concluding related to the character education values contained in Character Education in the Short Story Collection "Ihwal Nama Majid Pucuk" by T. Agus Khaidir. Based on the analysis, the short story collection Ihwal Nama Majid Pucuk by T. Agus Khaidir comprehensively contains 18 character education values according to the Ministry of National Education, including religious, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, national spirit, love of the homeland, respect for achievement, friendly/communicative, love of peace, love of reading, care for the environment, care for society, and responsibility. These values are conveyed implicitly through character conflicts, storylines, social settings, and narrative symbols that reflect the reality of life.